Graphical Tool for Positioning of Triads in Mechanisms - Antonya, Csaba (IOP Publishing, 2020)
The position of a triad (Assur group of class 3 and order 3) in a planar mechanism requires the computation of three parameters of the composing links. This can be obtained with analytical of graphical solutions. In this paper a graphical (or geometrical) solution is proposed, in which several 3D surfaces are generated with the geometrical parameters of the triad. The intersections of these surfaces will generate 3D curves and the solution of the problem will be the coordinates of a point at the intersection of a curve and a surface. This method can be applied regardless of the type of pairs in the triad. The advantage of the proposed geometrical method is that it offers a quick observable design of complex mechanisms in the analysis and synthesis process.